Contribution of Public e-Procurement to Sustainable Development Goals in Indonesia: Systematic Literature Review - Leny Marita; Nurita Andriani; Muhammad Alkirom Wildan; Yahya Surya Winata; Muhammad Syarif; Muhtadin Muhtadin; Muhammad Azmi Alamsyah (Universitas Trunojoyo Madura, 2021)
The Sustainable Development Goals have become the UN's global goals in the 2015 to 2030 time frame. To achieve these goals, Indonesia has designated a National Roadmap for Sustainable Development Goals in Presidential Regulation Number 59 of 2017. The Presidential Regulation serves as a guideline for Ministries or Agencies in National Actions Plans on Sustainable Development Goals in their respective domains. Including in the Public Procurement of Goods/Services has been fostered to increase sustainable procurement. This Systematic Literature Review has been looking for research evidence to reveal the contribution of e-procurement in the Sustainable Development Goals in Indonesia for the last decade. The evidence has been systematically collected by following the SLR protocol from the indexing Portal Garuda (Garba Rujukan Digital) specific for published articles in Indonesia. Meanwhile, the international research on sustainable procurement has been ongoing since 2001; the review here shows that there has not been much research on sustainable procurement in Indonesia. The results of this review offer a future research agenda for sustainable procurement in Indonesia.